Characterization and implication of phytolith-associated potassium in rice straw and paddy soils. Issue 10 (24th August 2019) - Nguyen, Huan X.; Nguyen, Van T.; Tran, Chinh T.; Nguyen, Anh T. Q.; Nguyen-Thanh, Lan; Bui, Anh T. K.; Dultz, Stefan; Wu, Ta Yeong; Nguyen, Minh N.
ABSTRACT: Rice straw contains up to 2.3% K in dry matter, including potassium (K) subcompartmented in phytoliths, complex siliceous structures formed in plant tissue via precipitation of Si. Rice straw is usually returned to the soil as a conventional practice to sustain soil nutrients, and therefore, the K pool accompanied with rice straw phytoliths is also cycled. Based on phytoliths obtained by ashing of rice straw at 400 °C and dissolution experiments using batch extraction in combination with physical separation of phytoliths by heavy liquid, this study evaluated the phytolith K(phytK) pool in rice straw and aged phytoliths in paddy soils. Entrapped organic matter containing K within phytolith silica cells was visualized by X-ray tomographic microscopy, and releases of this phytK pool accompanying phytolith dissolution were quantified. A 1% Na2 CO3 solution, which has been commonly used to extract amorphous Si and to quantify soil phytoliths, showed obvious responses for K derived from phytolith dissolution, indicating that the Na2 CO3 method can be developed for measurement of phytK. In 13 soil samples, Na2 CO3 -dissolvable K content assignable to phytK was 0.55 ± 0.39 g kg −1 in the puddled horizon, suggesting the phytK pool is of high significance for the management of K in paddy soils.